Understanding the pubertal, psychosocial, and cognitive developmental trajectories of stunted and non-stunted adolescents: protocol of a multi-site Indonesian cohort study - Medise, Bernie Endyarni; Julia, Madarina; Devaera, Yoga; Sitaresmi, Mei Neni; Asmarinah,; Widjaja, Nur Aisiyah; Kalalo, Royke Tony; Soesanti, Frida; Friska, Dewi; Sirait, Wani Riselia; Azzopardi, Peter; Sawyer, Susan (Frontiers in Pediatrics, 2024)
Background: The prevalence of stunting among Indonesian children aged 5-12 years decreased from 30.7% in 2013 to 23.6% in 2018, but remained among the highest rates worldwide. Furthermore, Indonesian children were shorter than the standard reported by the WHO and suffered from obesity. The Indonesian government has created many programs to reduce stunting in children under the age of five. An early preventive strategy is necessary because stunting can manifest within the initial one thousand days of life, including pregnancy. Therefore, a newer perspective, such as that achieved by addressing stunting in adolescents has been deemed useful, given that adolescents are in their pubertal stage and are undergoing lifestyle changes. This cohort study was designed to measure these factors comprehensively in stunted and non-stunted children as they pass through adolescence. Methods and design: For the prospective cohort, 560 individuals will be recruited from DKI Jakarta, DI Yogyakarta and East Java. The participants will be categorized into stunted and non-stunted groups, then undergo annual examinations in which key objectives, such as weight, height, and BMI will be assessed for the growth profile; waist circumference, middle-upper arm circumference, hand-grip strength, body fat percentage, and food intake will be evaluated in nutritional assessment; psychosocial and mental issues will be evaluated according to behavioral problems, symptoms of depression, quality of life, sleep patterns, anxiety disorders, and parenting style through the use of specific questionnaires; and pubertal stage will be assessed by a self-report questionnaire. Some cross-sectional data, such as cognitive performance, hair zinc levels, vitamin D levels, bone mineral density, and bone age, will also be included. All the outcomes will be analyzed in accordance with the variable types. Discussion: This study provides a thorough dataset of Indonesian adolescents encompassing several elements, such as growth, nutrition, psychosocial well-being, mental health, and pubertal development, for both stunted and non-stunted individuals. The data acquired from this study can be used to formulate policies to prevent stunting through targeted interventions for adolescents. Finally, a better understanding of adolescent health could lead to improved strategies to decrease the number of stunted individuals in the next Indonesian generation.